Ação antiinflamatória da lectina de semente de dioclea violacea na artrite induzida por zymosan - Paim, Luciana Brandão (2006)
Plant-derived lectins inhibit neutrophil chemotaxis, probably through a competitive mechanism with endogenous selectins for a glycosidic residue in the membrane of endothelial cells, leukocytes or in components of the extracellular matrix. We investigated the effects of a lectin isolated from Dioclea violacea (Dviol) seeds in the zymosan-induced arthritis (Azy). Wistar rats (180 a 220g) received an intraarticular (i.a.) injection of 1 mg zymosan (Zy) into the right knee. The hyperalgesia was evaluated with the test for articular incapacitation, measured as the paw elevation time (PET) in s/1min. Cell influx (IC) was assessed in the joint exudate, obtained 6 h after injection of the Zy, through washing and aspiration of the joint. Groups were pretreated 30min before the Zy with Dviol (1 - 30 µg; i.a. ou 1 - 10mg/kg; e.v.), and were compared to non-treated groups (NT), that received the Zy and the vehicle. Others groups received only Dviol (0,3 - 30µg; i.a. and the naïve animals (NV) received just saline i.a. The i.v. administration of Dviol (6mg/kg) significantly reduced the hyperalgesia (p<0.01) (PET= 14,08 ± 1,4) as compared to NT (PET= 36,06 ± 3,3). The i.v. injection of Dviol inhibited IC (18.266,7 ± 1.890,1; 14.633,3 ± 3.207,2; 2.790 ± 503,3 e 120 ± 37,4 cells/mm3 for the 1, 3, 6, and 10mg doses of Dviol, respectively). Dviol given i.a. isolated (30µg) increased PET (15,5 ± 0,9) significantly, as compared to NV. Dviol i.a. isolated (0,3 - 30 µg) significantly increased IC (3.600 ± 676; 4.958,3 ± 1037,2 e 8.350 ± 1.511,5 cells/mm3 for 0,3, 3 e 30 µg, respectively), as compared to NV (858,3 ± 389,5 cells/mm3). Dviol (10 µg i.a.) given 30min before the Zy significantly inhibited the hyperalgesia (PET = 20,15 ± 2,2) (p<0.01), as compared to NT (TSP= 9,9 ±1,2). Dviol i.a. (1, 10, and 30μg) significantly reduced IC (18.266,7 ± 1.890,1; 11.366,7 ± 2.883,7 e 19.866,7 ± 1.783,4 cells/mm3, respectively), as compared to NT. The i.v. administration of Dviol (6 mg/kg) + manose reversed the inhibitory action of Dviol in the hyperalgesia (PET= 38,4 ± 4,4) (P<0.01) and in the IC (15200 ± 1829,7 cells/mm3) of the AZy, as compared to Dviol (6mg/kg; i.v.) (TEP= 14,08 ± 1,4 and IC= 2.790 ± 503,3 cells/mm3). The results demonstrate, for the first time, that the lectin isolated from Dviol has anti-inflammatory effect in an experimental arthritis model. This effect appears to be prominently due to the coupling of Dviol to intrarticular polysaccharide residues. However, we can not exclude that coupling to protein residues may be also involved in this mechanism.